Determining rates of death in custody in England and Wales - Botchway, Stella (The journal of forensic psychiatry & psychology, 2022)
In England and Wales, there has been considerable work over recent years to reduce the numbers of deaths in custody. Currently, there is no standard, internationally agreed definition of a death in custody, which limits comparisons. In addition, rates of death in custody are often reported per country or region inhabitants, but it would be more useful to report per number of detainees. In this short communication, we present data on deaths in individuals who have been detained in England and Wales between 2016 to 2019. We also present a method to calculate rates of death per custodial population in key settings using routine data, allowing for more consistent comparisons across time and different settings. Most deaths in custody between 2016–2019 occurred in prisons (56% of all deaths in custody over 2016–19; Table 1). However, when rates are considered, those detained under the Mental Health Act had the highest rate of deaths, which ranged from 1103–1334/100,000 persons detained. Around one in five deaths were self-inflicted. The data presented highlights the need to maintain focus on improving the physical health and mental health of all those detained in custody, both whilst in detention and after release.